Preparation of a Sulfo‐Group‐Containing Rod‐Like Polysilsesquioxane with a Hexagonally Stacked Structure and Its Proton Conductivity. Issue 30 (20th June 2014) - Kaneko, Yoshiro; Toyodome, Hisaya; Mizumo, Tomonobu; Shikinaka, Kazuhiro; Iyi, Nobuo
Abstract A sulfo‐group‐containing rod‐like polysilsesquioxane with a hexagonally stacked structure (PSQ‐SO3H) was successfully prepared by oxidation and hydrolytic polycondensation of 3‐mercaptopropyltrimethoxysilane (MPTMS) in a mixed aqueous solution of NaOH and H2O2. The X‐ray diffraction pattern of the PSQ‐SO3H film exhibited three diffraction peaks with a d‐value ratio of 1:1/√3:1/2, indicating the formation of a hexagonally stacked structure. In addition, the transmission electron microscopy image of PSQ‐SO3H exhibited a striped pattern, indicating that the rod‐like PSQs were stacked in a parallel fashion. The presence of ionic side‐chains composed of the sulfonate anions and sodium cations during the hydrolytic polycondensation of MPTMS was found to be essential for the formation of this regularly structured PSQ. Finally, the proton conductivity of the PSQ‐SO3H film, determined by using complex impedance spectroscopy, was relatively high (>10−2 S cm−1) at 80 °C and 30–90 % relative humidity.